Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Produk pada McDonald’s di Jatiasih Bekasi - Basith, Abdul; Fadhilah, Faris (Jurnal Manajemen dan Organisasi, 2018)
The development of new era leads people to be fast and practical person on all activity. Include culture of choosing food and drink consumers choose fast food. The purpose of this study was to identify the characteristics of consumers, analyze the purchasing decision making process, and analyze the factors that influence consumer decision making. The method used in this research is a descriptive analysis and factor analysis use SPSS 25 for windows. The research result consumers characteristic at McDonald’s Jatiasih is female, last education senior high school, job as students and ten major factors influence consumer purchase decisions at McDonald’s, the factors consist of enviroment impact, the habits of individuals, marketing mix, activity, time, product attractiveness, knowledge and physical condition. Time factor is the strongest factors impact consumers buyer decision and dayime is the priority factors.